The Crucial Points of Subtextual Analysis in Contemporary Literary Criticism - Pasopati, Rommel Utungga; Wijaya, Kusuma; Andharu, Devito; Fadillah, Muhammad Reza Ishadi; Ananta, Bintang Ryan (CV. Tripe Konsultan, 2024)
This paper explores the crucial aspects of subtextual analysis in contemporary literary criticism. Modern literary criticism tends to play on the definitional aspects of literary works, but subtextual analysis goes beyond by regarding implied meanings. The idea is that meanings are waiting to be revealed by the audience. Through explorative approach and qualitative method, the analysis of this article revolves on the strategies, the critical roles, and the instance of subtextual analysis in literary analysis. The strategies of subtextual analysis involve engaging the audience to foster a personal connection with literary works, synthesizing and correlating meanings within literary works, encompassing empathetic engagement with the narrative, and developing diverse perspectives from the audience's vantage point. The critical roles of subtextual analysis consist of facilitating deeper implications through insinuated meanings, enhancing meanings in intrinsic and extrinsic dimensions of literary works, unveiling repressions presented within the text, facilitating exploration of anticipated interpretations and underlying meanings, adopting interdisciplinary approach, engaging with societal dimensions of literary works, perceiving literary works beyond any definition, and propelling co-texts, hypertexts, hypo-texts, and intertexts. In conclusion, subtextual analysis underlines possibilities in literary analysis by comparing various implied meanings related to humans’ identities in particular.